Gambaran Kualitas Pelayanan Tenaga Administrasi di Puskesmas Kepala Gading Jakarta Utara Tahun 2024 - Purwanty Elizabeth Lawalata; Ria Efkelin; Yurita Mailintina (Journal of Educational Innovation and Public Health, 2026)
Services in the health sector are a form of public service that must be implemented properly by the government. In the context of health services, the importance of effective and efficient implementation cannot be ignored because this has a direct impact on people's quality of life. In order for health services to achieve their goals, various requirements must be met, including the availability of adequate facilities and infrastructure, a harmonious relationship between patients and service providers, easy accessibility, and high quality. The aim of this research is to determine the description of the service quality of administrative staff. at the Kelapa Gading Community Health Center. The method used is descriptive with a quantitative approach which produces univariate results. This research was conducted at the Kelapa Gading Community Health Center with a total of 150 respondents. The variables in this research are Service Procedures, Completion Time, Service Costs, Service Products, Facilities and Infrastructure, Accreditation of Service Officers. The population in this study were all 1.216 outpatients with a sample of 150 respondents.